2018
DOI: 10.1055/a-0725-9297
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Thyroid Autoimmunity: A Personal Overview from the Past into the Future

Abstract: After investigating thyroid autoimmunity for more than 40 years, we present a personal perspective on the field. Despite effective therapies for Graves’ hyperthyroidism and Hashimoto’s thyroiditis, cures are elusive. Novel forms of therapy are being developed, such as small molecule inhibitors of the TSH receptor (TSHR), but cure will require immunotherapy. This goal requires advances in understanding the pathogenesis of thyroid autoimmunity, the ‘keys’ for which are the thyroid antigens themselves. Presently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 146 publications
1
13
0
Order By: Relevance
“…For two centuries GD has been known for its clinical characteristics and the evolution of its knowledge derived from seminal contributions of several authors (Flaiani, Parry, Graves and von Basedow) [11]. The clinical picture of GD is now summarized in the 'GD triad' , consisting of hyperthyroidism, orbitopathy (Graves' eye disease) and dermopathy (pre-tibial myxedema) [12]: the multiple clinical forms of GD (from highly localized thyroid disease to systemic extrathyroidal autoimmune disease, involving retro-orbit, skin and bone) [13] are now considered explicable by the variable forms of the TSHR interested by immune activation (monomeric or dimeric), the heterogeneous sites of TSHR expression (thyrocytes, fibroblasts, adipocytes, bone cells, and other cell types) and the multiplicity of biochemical signals and pathways employed by TSHR (G protein dependent or G-protein independent) [14]. TSHR is a member of class A family of G-protein coupled receptors (with the close relatives follitropin and lutropin/choriogonadotropin receptors) that is essential for the function and growth of the thyroid gland and activates different signaling pathways required for thyroid hormones synthesis and release.…”
Section: Graves' Disease and Tsh Receptormentioning
confidence: 99%
See 1 more Smart Citation
“…For two centuries GD has been known for its clinical characteristics and the evolution of its knowledge derived from seminal contributions of several authors (Flaiani, Parry, Graves and von Basedow) [11]. The clinical picture of GD is now summarized in the 'GD triad' , consisting of hyperthyroidism, orbitopathy (Graves' eye disease) and dermopathy (pre-tibial myxedema) [12]: the multiple clinical forms of GD (from highly localized thyroid disease to systemic extrathyroidal autoimmune disease, involving retro-orbit, skin and bone) [13] are now considered explicable by the variable forms of the TSHR interested by immune activation (monomeric or dimeric), the heterogeneous sites of TSHR expression (thyrocytes, fibroblasts, adipocytes, bone cells, and other cell types) and the multiplicity of biochemical signals and pathways employed by TSHR (G protein dependent or G-protein independent) [14]. TSHR is a member of class A family of G-protein coupled receptors (with the close relatives follitropin and lutropin/choriogonadotropin receptors) that is essential for the function and growth of the thyroid gland and activates different signaling pathways required for thyroid hormones synthesis and release.…”
Section: Graves' Disease and Tsh Receptormentioning
confidence: 99%
“…Recently, starting from the knowledge of the molecular structure of TSHR, promising results have been highlighted by the use of an antigen-specific immunotherapy of Graves' disease and Graves' orbitopathy, using small amounts of synthetic peptides derived from the TSH receptor, that mimic naturally processed CD+T cell-epitopes [64,65]. This first demonstration of the effectiveness of a specific therapy, which induces immunotolerance for Graves' endocrinopathy [13], paves the way for new therapeutic approaches in many, if not all, autoimmune receptor diseases.…”
Section: Implications For Therapeutic Use Of Receptor Peptides and Aumentioning
confidence: 99%
“…Most recently, we also focused on thyroid diseases, e. g. autoimmune thyroid disease; here another three special issues were published highlighting the genetic cause as well as the immunological background, diagnostic procedures and therapeutic options in Graves' disease and autoimmune thyroiditis, including a most recent special issue [16][17][18][19][20][21][22][23][24].…”
Section: Dear Readersmentioning
confidence: 99%
“…Thyroid health problems may be indicated by increased levels of thyroid-related antibodies, including thyroglobulin antibodies (TgAb) and anti-thyroid peroxidase (anti-TPO). The presence of these antibodies has been associated with a diagnosis of autoimmune disease of the thyroid [22,23], although anti-TPO is a more specific marker for autoimmune thyroiditis than TgAb [24]. Kim et al found that while anti-TPO was not associated with thyroid malignancy, positive TgAb could predict thyroid cancer in patients with thyroid nodules [24].…”
Section: Introductionmentioning
confidence: 99%